Interim report on the soils inventory of the AOSERP study area - Lindsay, J. D.; Turchenek, L. W. (1979)
Soil mapping of the AOSERP study area using the ecological or biophysical approach to land classification was continued in 1978. Work consisted of air photo interpretation, field checking, preparation of interim maps, and analysis of soil samples. About 150 townships were field checked during the summer field season, and samples were taken from 44 mineral and 20 organic soil profiles. Samples collected from 52 profiles during the 1977 field season were analyzed during 1978. Since the initiation of this project, about 700 soil samples have been collected for laboratory analysis. The number of interim maps produced to date, including 16 submitted with this report (but which will be published separately at a later date) is equivalent to 12 of the 1:50 000 National Topographic Services (NTS) sheets within the high priority area. With new field and laboratory data, the legend was revised and now describes 21 land systems. Significant findings include the occurrence of Solonetzic soils on the Dover Plains, and of extensive areas of permafrost in organic soils of the Birch Mountains Upland and the Dunkirk Plain.